Signal processing for multistatic radar systems : adaptive waveform selection, optimal geometries and pseudolinear tracking algorithms /: adaptive waveform selection, optimal geometries and pseudolinear tracking algorithms. (2019) - Nguyễn, Ngọc Hùng; Doğançay, Kutluyıl
No abstract available